2012
DOI: 10.1371/journal.pone.0040364
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Expression of the ARID1A Gene Is Associated with Poor Prognosis in Primary Gastric Cancer

Abstract: BackgroundThe ARID1A gene encodes adenine-thymine (AT)-rich interactive domain-containing protein 1A, which participates in chromatin remodeling. ARID1A has been showed to function as a tumor suppressor in various cancer types. In the current study, we investigated the expression and prognosis value of ARID1A in primary gastric cancer. Meanwhile, the biological role of ARID1A was further investigated using cell model in vitro.Methodology/Principal FindingsTo investigate the role of ARID1A gene in primary gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
118
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(126 citation statements)
references
References 24 publications
8
118
0
Order By: Relevance
“…Loss of ARID1A expression was found to be an adverse prognostic factor in gastric cancer, 9 cervical cancer 33 and endometrial clear cell carcinoma. 6 In ovarian clear cell carcinoma, the prognostic effects of ARID1A expression were inconsistent in different studies by Shih et al 10 and Katagiri et al 34 Both our study and Shih's study revealed that ARID1A expression was not a prognostic factor for ovarian clear cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Loss of ARID1A expression was found to be an adverse prognostic factor in gastric cancer, 9 cervical cancer 33 and endometrial clear cell carcinoma. 6 In ovarian clear cell carcinoma, the prognostic effects of ARID1A expression were inconsistent in different studies by Shih et al 10 and Katagiri et al 34 Both our study and Shih's study revealed that ARID1A expression was not a prognostic factor for ovarian clear cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…4 ARID1A is a tumorsuppressor gene located at 1p36, which is frequently mutated in ovarian, endometrial, breast, urinary bladder and gastric cancers. [5][6][7][8][9] In gynecologic cancers, ARID1A promotes formation of SWI/SNFmediated chromatin remodeling and is present in 46% of ovarian clear cell carcinomas and 30% of endometrioid carcinomas. 5,24 In our study, we confirmed that loss of ARID1A expression was cell carcinoma, and can be caused by either PIK3CA mutations, PTEN loss or a combination of these alterations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…55 In gastric cancer, knockdown of wild-type ARID1A in four gastric cancer cell lines enhanced proliferation, whereas restoring ARID1A expression suppressed tumor proliferation in three ARID1A-deleted gastric cancer cell lines. 45,75 In bile duct cancer, silencing of ARID1A in three cell lines with wild-type ARID1A resulted in increased proliferation, which was reversed when ARID1A was re-expressed ectopically. 51 In hepatocellular carcinoma, ARID1A knockdown significantly promoted cellular proliferation of four wild-type cell lines but did not affect a cell line with ARID1A mutation.…”
Section: Arid1a As a Gatekeepermentioning
confidence: 99%
“…In gastric cancer, an association has been described between MSI and mutations in ARID1A. 12,[14][15][16] As the rate of somatic ARID1A mutations in MSI cases was 12-to 61-fold higher than the global background mutation rate, it was suggested that the ARID1A gene is particularly targeted by MSI. 12 A possible association between ARID1A loss and MSI, as has been reported for gastric cancer, has not been studied in endometrial cancer.…”
mentioning
confidence: 99%